Bringing the Past to Life: Teaching English Grammar Through Folklore and Visual Storytelling in Indonesian Classrooms - Idris Sadri; Alvindi Alvindi (Program Studi Pendidikan Bahasa Inggris FKIP Universitas Muslim Maros, 2025)
Teaching English grammar, particularly tenses, presents a significant challenge in the Indonesian context, where traditional methods often fail to engage students effectively. This study investigates the use of Indonesian folklore combined with visual aids as a strategy for teaching the English simple past tense. The research explores the potential of integrating culturally relevant content with pictures to enhance grammar acquisition and student engagement. A mixed-methods approach was employed, consisting of pre- and post-tests, classroom observations, and student surveys. The findings reveal that students exposed to folklore and picture-based instruction showed a 24% improvement in grammar comprehension, significantly outperforming their peers in the control group, who received traditional grammar instruction. The experimental group also exhibited higher levels of engagement, with students demonstrating greater enthusiasm and active participation in learning activities. These results suggest that culturally contextualized materials, coupled with visual aids, foster a more interactive and enjoyable learning environment, ultimately improving students' ability to apply grammatical structures in real communication. This study highlights the potential of folklore as a pedagogical tool, offering valuable insights for enhancing grammar instruction and motivating learners in the Indonesian educational context.